ChemInform Abstract: Synthesis of Novel Dispiro[acenaphthylene‐pyrrolidine‐pyrrolizine] Derivatives via a 1, 3‐Dipolar Cycloaddition of Azomethine Ylide. Issue 24 (2nd June 2014) - Liu, Bin; Li, Xiaofang; Du, Liyun; Li, Zhikui; Zeng, Rongjin
Abstract generated in situ from acenaphthenequinone (IV) and sarcosine with 2‐arylidenepyrrolizinone derivatives (III)